Deaf education and art teaching in the context of the bilingual school - Andrade, Renan de Bastos (2023)
The teaching of art in the early years of Elementary School presents the four languages ​​(Visual Arts, Dance, Music, and Theater) in an integrated way and from a playful perspective. The study aims to analyze the teaching of art in the education of deaf children from the bilingual school perspective. The research is qualitative and interpretive. A teacher and seven students from a deaf bilingual school in Paraná participated in the study. The data were analyzed using a qualitative approach. The data collection instruments were observation, interviews and application of activities, content analysis perspective of content analysis. Concluded that teaching  art to deaf students must occur from the beginning of their schooling. Through this art, they find a way to affect their communication, demonstrate feelings, and construct meanings. It highlights the importance of teaching art in a bilingual school’s classrooms and how much this subject can contribute to the educational development of deaf students.